Languages in Education: A Critical Ethnography of a Micro-level Policy - Kandel, Basanta (Journal of NELTA, 2021)
This article explores the language policy in education (henceforth, LPE) at the local level. Adopting the critical ethnography study for 6 months at Vyas Municipality, I reveal what ideological awareness the policymakers and arbiters have on LPE and how do they interpret and appropriate it in multilingual school setting. The information collected through in-depth interviews, FGD, participant observation, and document reviews have been analyzed, interpreted, and triangulated critically. The study shows three major findings regarding LPE in local government; first, LPE has created a public debate and ideological discrepancy in multilingual school contexts; the second, the local LPE has diverse interpretation, appropriation, and practices; and the last, the English language policy (ELP) appears as a ‘black hole’, which has been gradually swallowing other local and indigenous languages. However, the language policymakers and arbiters have been gradually raising critical awareness for appropriate LPE and its practices that seems a positive advancement at the local level.